COVID-19, Anxiety, and Hopelessness: Quality of Life Among Healthcare Workers in Turkey. Issue 1 (March 2022) - Mert, Selda; Peker Karatoprak, Ayfer; Demirhan, Yeliz; Baydemir, Canan; Çetinarslan, Berrin; Cantürk, Zeynep; Selek, Alev; Aydin, Levent; Sözen, Mehmet; Gezer, Emre
The aim of the study is to investigate the effects of intense anxiety and hopelessness experienced by healthcare workers during the pandemic on their quality of life. This cross-sectional, online questionnaire-based study was conducted between August 31, 2020 and October 31, 2020, with 729 healthcare workers in Turkey. The study showed that hopelessness, the weekly working time, fatigue, and the workload of healthcare workers negatively affected their quality of life, those who found the pandemic measures inadequate had a lower quality of life and higher hopelessness levels, and those who needed knowledge on various issues to improve their skills had lower quality of life and higher levels of anxiety and hopelessness. Increasing the measures to make healthcare workers feel competent and ready during the COVID-19 pandemic and meet their information needs to improve their skills will reduce their anxiety and hopelessness and improve their quality of life. Identifying the factors affecting anxiety, hopelessness, and quality of life will help achieve sustainable success in the delivery of health services and promote employee health and safety.